A Study of the Effects of Wetland Degradation on Soil-Microbial-Extracellular Enzyme Carbon, Nitrogen, and Phosphorus and Their Ecological Stoichiometry - Ye Li; Jiuwang Jin; Shuangyi Li; Shuhao Xia; Jianbing Wei (Agronomy)
Due to the unique geographic location of A’er Xiang, there is a natural landscape where sandy land and lake-marsh wetlands coexist. However, the wetland degradation caused by the disturbance of anthropogenic activities has led to the change in land use. In this study, the spatial-temporal substitution method was used to select five sample plots: the original wetland converted to forest land for reuse area of five years and ten years; the original wetland converted to cropland for reuse area of five years and ten years; and the native wetland. It aims to investigate the variations in carbon, nitrogen, and phosphorus and their stoichiometric characteristics of soil-microorganisms-extracellular enzymes before and after reuse, and to analyze potential interactions among these elements. The results indicated that following wetlands degradation, changes in land use for five years did not significantly affect the content of soil organic carbon (TOC), total nitrogen (TN), or total phosphorus (TP). However, after ten years, both TOC and TN, except for TP, decreased significantly. Microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) contents in cropland were consistently higher than those in WL, showing a trend of first increasing and then decreasing with longer conversion periods. In contrast, forest land values were lower than in WL and increased as the conversion period lengthened. The microbial biomass phosphorus (MBP) content was ranked across the five sample sites as follows: 10 CL > 5 CL > 5 FL > 10 FL > WL. β-1,4-glucosidase (BG) activity was significantly increased after conversion to forest land and significantly decreased after conversion to cropland. β-1,4-N-glucosidase (NAG) and L-leucine aminopeptidase (LAP) activities were ranked as follows among the five sites: 5 FL > WL > 5 CL > 10 FL > 10 CL. Phosphatase (PHOS) activity showed no significant changes post-conversion, though it was consistently lower compared to WL.